THE INTERSECTION OF TECHNOLOGY AND SOCIAL CHANGE: EXPLORING THE IMPACT OF DIGITAL MEDIA ON MODERN POLITICAL MOVEMENTS - Dr. Ahmed Ali (Modern American Journals, 2025)
Digital media has significantly transformed modern political movements, providing activists and organizations with unprecedented tools for mobilization, communication, and global reach. This paper explores the intersection of technology and social change, specifically examining the role of digital media in shaping contemporary political movements. From the Arab Spring to the Black Lives Matter movement, social media platforms such as Twitter, Facebook, and Instagram have enabled political actors to engage in real-time communication, challenge traditional power structures, and mobilize supporters across borders. However, the digital revolution also introduces challenges related to misinformation, censorship, and surveillance. This research investigates the dual-edged nature of digital media in political activism, highlighting both its empowering potential and the risks it poses to democratic engagement.
Keywords: Digital Media, Political Movements, Social Change, Activism, Social Media, Globalization, Mobilization, Surveillance, Misinformation, Technology.